Microsoft Office Team 365 for Teaching Indonesian Language in Secondary Schools During COVID-19 Pandemic - ., Asropah (KnE Social Sciences, 2022)
The COVID-19 outbreak has led to many changes in Indonesia. One of the strongest changes has been felt in the Indonesian language teaching and learning process. Presenting interactive media is on-demand to maintain students’ engagement in learning. Microsoft Office Team 365 is an application that allows the teacher and the students to interact with each other during distance learning. This study exposes the implementation of Microsoft office Team 365 for teaching the Indonesian language in five secondary schools in Semarang as well as the barriers faced by the teachers and students. The authors found that the Microsoft Office Team 365 features are utilized well to keep the students engaged in the Indonesian language learning process. Keywords: Microsoft Office Team 365, Indonesian language learning, COVID-19 pandemic